Management of Spodoptera exigua on shallots in several areas of Indonesia using mating disruption with different pheromone doses - Witjaksono; Soffan, Alan; Wijonarko, Arman; Martono, Edhi; Wagiman, F.X.; Putra, Nugroho Susetya; Harjaka, Tri; Indarti, Siwi; Suputa; Trisyono, Y. Andi (Agriculture and Natural Resources, 2023)
Importance of the work: The continuous use of insecticides with the same active ingredient has resulted in the growth of insecticide-resistant Spodoptera exigua moth populations that can accumulate in shallot tubers. Objectives: To investigate the effectiveness of using pheromones as a mating disruption approach in managing S. exigua. Material & Methods: This study was carried out in Bantul, Nganjuk and Kulon Progo, Indonesia. In Bantul, 500 dispensers/ha were installed together with a control. In Ngajuk, 100 dispensers/ha, 200 dispensers/ha and 300 dispensers/ha were installed togeteher with a control. In Kulon Progo, 100 dispenser/ha were installed, together with a control. All treatments were replicated three times. Result: Pheromone installation of 500 dispensers/ha in Bantul disrupted the S. exigua males from locating the females. The effectiveness of sex pheromones was also observed in Nganjuk (300 dispensers/ha, 200 dispensers/ha and 100 dispensers/ha) and in Kulon Progo (100 dispensers/ha). These experiments showed that disrupting the male-female communication was successful because male-female encounters in the treatment plots were reduced. Hence, the eggs of the S. exigua females were not fertilized and fewer eggs hatched. However, the effectiveness of disrupting the male-female communication decreased when the moth population in the field was high. Main finding: The installation of pheromone at dosages of 100 dispensers/ha, 200 dispensers/ha, 300 dispensers/ha and 500 dispensers/ha disrupted male-female communication among low populations of S. exigua . Installation of pheromone in 100 dispensers/ha could be a favorable option for farmers because it had the lowest materials cost. The placement of the pheromone dispensers around the field perimeter should be considered because it might hinder S. exigua from entering the field. Additionally, using pheromones before planting could serve as a control technique.